Stopp, inte min kropp: Om kriminaliseringen av pornografiska deepfakes i Sverige - Backman,Oliver (2024)
With technological advancements come new possibilities for the digital age, but also the risk of a new kind of violations of personal and sexual integrity. A recent development that constitutes an especially pressing threat to the integrity of individual persons is the ability to create pornographic deepfakes, AI-generated pornographic material of an individual person. This essay examines to what extent an individual person in Sweden is protected against the generation and spread of pornographic deepfakes. The work employs a legal dogmatic method and attempts to discern which actions concerning the creation and spread of pornographic deepfakes are prohibited under Swedish law, in order to determine the legal response to such violations. The essay explores in what way the protection of personal integrity in the Swedish Penal Code (Brottsbalken (1962:700)) is applicable in addressing the violations caused by pornographic deepfakes, and finds that Swedish law holds some ambiguities concerning the applicability of such protections on material of that kind. Concerning the spread of pornographic deepfakes it is found that further clarifications are needed regarding the legal impact of the body depicted in deepfake material not actually being the body of the depicted person. As for the generation of pornographic deepfakes for private use it is found that due to the protection of freedom of expression and information, there is currently no real protection against being depicted in such material, but that the criminalization of such actions would have some support in current Swedish law and that a coherent and effective protection of personal integrity demands that the generation of pornographic deepfakes for personal use is limited. The essay suggests that Swedish law be updated in order to expand upon the protection of personal integrity, in order for such protection to properly address advancements in technology.
Keywords: straffrätt; artificiell intelligens; deepfakes; personlig integritet